KOMPOSISI SENYAWA ISOPRENOID PADA MANGROVE SEJATI MINOR JENIS TERUNTUN (Aegiceras corniculatum (L.) Blanco) SEBAGAI BIOMARKER DI DAERAH ESTUARINA - Julayha Julayha; Mohammad Basyuni; Lollie Agustina (Peronema Forestry Science Journal, 2012)
This study described the analyzing of composition and diversity of triterpenoid and phytosterol in North Sumatera mangrove species A. corniculatum as biomarkers and input lipids in to estuarine ecosytem. Phytosterols found  in the  roots and leaves of A. corniculatum were stigmasterol, campesterol, β-sitosterol, and cycloartenol. Taraxerol, β-amyrin, germanicol, betulin, α-amyrin, lopenone and lupeol were the triterpenoids identified. Betulin was the major component triterpenoids had the highest content (31,8%) in the  roots. This research may provide information  the composition of triterpenoid and phytosterol to contribute to estimating the lipid input and as biomarker  from                     A. corniculatum to estuarine ecosytem. Keywords : Mangrove, A.corniculatum (L) Blanco, Biomarker, Estuarine, and Lipid.